Proteinuria and Albuminuria at Point of Care. Issue 1 (2016) - Cassia, Matthias A.; Pozzi, Federico E.; Bascapè, Sara; Saggiante, Lorenzo; Daminelli, Giulia; Cirelli, Camilla; DamAV andi, Payam Tabaee; Elli, Marco; Gallieni, Maurizio
A case of proteinuria and albuminuria in a previously healthy 55-year-old male is described with discussion revolving around key questions: 1. What is the value of proteinuria assessment? 2. How is proteinuria defined? 3. Are urine dipsticks useful for proteinuria assessment? 4. What is the urinary albumin to creatinine ratio? 5. What about the urinary protein to creatinine ratio? 6. How do uACR and uPCR compare? 7. Is proteinuria assessment useful for predicting and monitoring CKD in diabetes and hypertension? 8. How do we test for tubular and overflow proteinuria? 9. Is physical exercise useful for our diabetic patient, despite the occurrence of proteinuria?